POSITIONING GARUDA INDONESIA BERDASARKAN PERSEPSI PENUMPANG RUTE PENERBANGAN SURABAYA - JAKARTA - Andrys Daud (UMSurabaya Publishing, 2014)
The positioning research is important doing by marketer while competition increases sharply in the industries. This research purposes to know the position of six airlines in the Surabaya-Jakarta flights in perceptual map. Garuda Indonesia and Batik Air has position as priority airline for full service carrier and the others (Air Asia, Citilink, Lion Air and Sriwijaya Air) for low cost carrier. This research shows that Garuda Indonesia tends had position relatively close from ideal brand position in the perceptual map.Keywords: Airlines competition, positioning,, ideal brand